Concluding comments: Some problems and comparisons - Sawyer, Peter (Hikuin, 1998)
The ‘critical and provocative’ comments that I have been asked to make will not be on the separate papers but on the conference as a whole. After some observations on the problems that can be encountered when experts in different disciplines use each other’s results, I will draw attention to some aspects of the wider background that are relevant to, and cast some light on, urban development in northern Europe.